Rekonstruksi Sistem Presidential Threshold dalam Sistem Pemilu di Indonesia: (Studi Perbandingan Sistem Presidential Threshold Indonesia dan Brazil) - Sinta Devi Ambarwati; M. Roziq Saifulloh; Stella M.S. Aritonang (Jurnal Hukum Lex Generalis, 2020)
Elections that are hereinafter referred to as elections are one part of the process as well as the result of a democratic system based on the doctrine of "power of the people", namely the power of the people, by the people, and for the people. In 2019, the election will be held simultaneously. The existence of this simultaneous election was born after the issuance of the Constitutional Court of the Republic of Indonesia No. 14 / PUU-XI / 2013 on The Testing of Law No. 42 of 2008 concerning Presidential and Vice Presidential Elections. However, there are some problems in the implementation of the 2019 election, namely the application of the concept of Presidential Threshold or threshold for presidential and vice presidential submissions. The implementation of this Presidential Threshold policy has a positive impact, one of which is the strengthening of the presidential system through simplification of political parties. However, the implementation of the Presidential Threshold can also lead to transactional politics between political parties. In addition, the Presidential Threshold is also considered to eliminate the right of citizens to vote (right to vote). Along with some of the weaknesses of the implementation of the Presidential Threshold, there is a need for an idea to regulate the Presidential Threshold policy so that in its application later in the 2019 Election there are no more contradictions that occur in the community regarding the existence of Presidential Threshold policies. This can be done by applying the concept of General Elections using the Presidential Threshold system simultaneously, but in its implementation later using the Closed Election system. The second alternative to accept the 2019 simultaneous elections, namely using the Presidential Threshold system and the Open Election system, but implemented gradually. The third uses the Presidential Threshold system of 0%.